2022
DOI: 10.1007/s12020-022-03198-2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with combined resveratrol and myoinositol ameliorates endocrine, metabolic alterations and perceived stress response in women with PCOS: a double-blind randomized clinical trial

Abstract: Purpose: The present study aimed to assess whether treatment with combined resveratrol and myoinositol is more effective in ameliorating the altered parameters associated with PCOS when compared to the combined metformin and pioglitazone therapy.Method: One hundred and ten obese, infertile PCOS women, aged 20-35 years were randomly assigned into two treatment arms. Participants in arm-1 (n=55), received combination of metformin and pioglitazone (1000 mg and 30 mg, respectively), once daily, while those in arm-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The results showed improvement in ovarian morphology, but due to the small sample size, more studies with larger participant numbers need to be conducted. Two additional randomized controlled trials on PCOS patients exploring the combinatory effect of resveratrol + myoinositol [162] and resveratrol + lipoic acid [163] were recently performed. Both studies observed beneficial effects on endocrine, stress, and metabolic parameters.…”
Section: Human Studiesmentioning
confidence: 99%
“…The results showed improvement in ovarian morphology, but due to the small sample size, more studies with larger participant numbers need to be conducted. Two additional randomized controlled trials on PCOS patients exploring the combinatory effect of resveratrol + myoinositol [162] and resveratrol + lipoic acid [163] were recently performed. Both studies observed beneficial effects on endocrine, stress, and metabolic parameters.…”
Section: Human Studiesmentioning
confidence: 99%
“…In a study involving 110 patients, the treatment with both RSV and myoinositol was substantially more efficient than metformin and pioglitazone in improving abnormal endocrine, metabolic markers and stress burden and has excellent potential in the high-risk category of obese, oligo-anovulatory women with PCOS [165]. Another inquiry established that the protective actions of RSV on ovulation in rats with PCOS are correlated to the modulation of glycolysis-dependent mediators, such as pyruvate kinase isozyme M2, lactate dehydrogenase A, and SIRT1 [166].…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…Apart from the above-mentioned studies, based on our understanding of VCP-MSP, antioxidant, antiinflammatory agents, such as dietary natural stilbenes polyphenol, Resveratrol (RV), can be a potential intervention in VCP-MSP. Resveratrol decreases apoptosis, inflammation, mitochondrial dysfunction, and helps improve lifespan with its antioxidant capabilities, and it has been safely used in several clinical trials [60][61][62]. Given the underlying mitochondrial pathology in VCP-MSP, including hindered ATP production, mitochondrial modifiers can be theoretically beneficial [63].…”
Section: Other Potential Therapiesmentioning
confidence: 99%